Aerosol effect on the evolution of the thermodynamic properties of warm convective cloud fields - Dagan, Guy (Sci Rep, 2016)
Convective cloud formation and evolution strongly depend on environmental temperature and humidity profiles. The forming clouds change the profiles that created them by redistributing heat and moisture. Here we show that the evolution of the field’s thermodynamic properties depends heavily on the concentration of aerosol, liquid or solid particles suspended in the atmosphere. Under polluted conditions, rain formation is suppressed and the non-precipitating clouds act to warm the lower part of the cloudy layer (where there is net condensation) and cool and moisten the upper part of the cloudy layer (where there is net evaporation), thereby destabilizing the layer. Under clean conditions, precipitation causes net warming of the cloudy layer and net cooling of the sub-cloud layer (driven by rain evaporation), which together act to stabilize the atmosphere with time. Previous studies have examined different aspects of the effects of clouds on their environment. Here, we offer a complete analysis of the cloudy atmosphere, spanning the aerosol effect from instability-consumption to enhancement, below, inside and above warm clouds, showing the temporal evolution of the effects. We propose a direct measure for the magnitude and sign of the aerosol effect on thermodynamic instability.